Mister, bro, or ada? styles of addressing among multilingual Pakistani students - Soomro, Muhammad Arif; Larina, Tatiana (Penerbit Universiti Kebangsaan Malaysia, 2023)
Address forms are an important component of communication with a wide range of socio-cultural differences across languages and cultures. In a multilingual context, their variety creates problems in comprehending their pragmatic meaning and appropriate usage. The study aims to define the categories of address forms used by multilingual Pakistani students speaking in English in an academic setting and to highlight the impact of socio-cultural context and identity on their choice in different situations. We have limited our study to the interaction between students in three social contexts and explored addressing a peer (a classmate), a junior student, and a senior student. The data were collected through a questionnaire with the participation of 252 students and were analysed with a mixed-method approach both quantitative and qualitative. Our results show that Pakistani students use a creative mixture of different categories of English and native address forms while speaking in English to express their values, attitudes, and identity. They demonstrate a strong sensitivity to the asymmetrical relations and adherence to hierarchy among junior and senior students resulting in variations of formality and informality. The findings illustrate the impact of context, values, and identity as well as the native language on address forms and their functioning in a bi-multilingual context and contribute to sociolinguistics, pragmatics, variational linguistics, bi-multilingualism, and cultural linguistics.